Invariant Submanifolds of Trans-Sasakian Manifolds - Anitha, B. S.; Bagewadi, C. S. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We prove the equivalence of total geodesicity, recurrence, birecurrence, generalized birecurrence, Riccigeneralized birecurrence, parallelism, biparallelism, pseudoparallelism, bipseudoparallelism of σσ for the invariant submanifold $M$ of the trans-Sasakian manifold $\tilde{M}$.